SCHOOL INCLUSION: SOME DISCUSSIONS IN MATHEMATICS EDUCATION - Capasio Rosa, Erica Aparecida [UNESP]; Baraldi, Ivete Maria [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
This article presents considerations about laws, dissertations and theses in the Graduate Program in Mathematics Education discussing this topic and some reflections on school inclusion from clippings of stories of teachers who teach mathematics in a municipality of Sao Paulo, Rose survey participants (2014). In this research were interviewed nine teachers, seven teachers of Mathematics and two teachers of Special Education. To provide these narratives was used as the methodology of Oral History. At the end we find that when we are talking about school inclusion, we are talking about another school model, as this where the teachers report and that there is still the rule, even unconsciously people with disability, pervasive developmental disorder, high abilities and giftedness
Keywords: Inclusive education mathematics; School; Students with disabilities; Teachers; Narratives